Implementation of Project-Based Learning Towards Reading Achievement of Eighth Grade Students at SMPN 20 Bengkulu City - Lestari, Lola; Hakim, Arif Rahman; Putra, Pebri Prandika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the effect of the implementation of Project-Based Learning (PjBL) on the reading achievement of eighth-grade students at SMPN 20 Bengkulu City. The PjBL model was chosen because it is believed to be able to increase students' involvement, creativity, and critical thinking skills through structured and contextual project activities. This study used a quasi-experimental method with a non-equivalent control group design. Data analysis was carried out through normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests using SPSS. The results showed that both the experimental and control groups experienced an increase in reading scores, but the increase in the experimental group was much more significant. The average pre-test score of the experimental group was 65.66 and increased to 78.48 in the post-test, while the control group increased from 61.10 to 73.93. The t-test showed a significance value of 0.007 (p < 0.05), so H₀ was rejected and H₁ was accepted. Thus, this study concludes that Project-Based Learning has a significant impact on improving students' reading skills, thus PBL can be recommended as an effective learning model for improving students' literacy competencies at the junior high school level.